Enhancing Robustness and Imperceptibility with a Texture-Based Adaptive QIM Approach - Awad, Jalal H. (Iraqi Journal of Science, 2024)
This paper proposes a new approach for image data hiding that aims to improve both robustness and imperceptibility. The proposed approach is based on a texture-adaptive quantization index modulation (QIM) method that takes into account the local characteristics of the image texture to optimize the embedding process. The approach is evaluated using various image datasets and compared to existing state-of-the-art techniques. The results show that the proposed approach achieves better performance in terms of robustness against various image processing attacks, with BERs of zero in some attacks, while maintaining a high level of imperceptibility with PSNRs exceeding 46 decibels. It can be deduced that adaptation and normalization of the embedding strength arguments can enhance the QIM methods’ performance. The proposed approach has potential applications in image authentication, copyright protection, and data hiding.